'I need time to start antiretroviral therapy': understanding reasons for delayed ART initiation among people diagnosed with HIV in Lusaka, Zambia'. (31st December 2022) - Mwamba, Chanda; Beres, Laura K.; Topp, Stephanie M.; Mukamba, Njekwa; Simbeza, Sandra; Sikombe, Kombatende; Mody, Aaloke; Geng, Elvin; Holmes, Charles B.; Kennedy, Caitlin E.; Sikazwe, Izukanji; Denison, Julie A.; et al.
Abstract: Introduction: Rapid antiretroviral therapy (ART) initiation can improve patient outcomes such as viral suppression and prevent new infections. However, not everyone who can start ART does so immediately. Methods: We conducted a qualitative study to inform interventions supporting rapid initiation in the 'Test and Start' era. We purposively sampled 20 adult patients living with HIV and a previous gap in care from ten health facilities in Lusaka, Zambia for interviews. We inductively analysed transcripts using a thematic, narrative approach. In their narratives, seven participants discussed delaying ART initiation. Results: Drawing on messages gleaned from facility-based counselling and community information, many cited greater fear of rapid sickness or death due to imperfect adherence or treatment side effects than negative health consequences due to delayed initiation. Participants described needing time to 'prepare' their minds for a lifetime treatment commitment. Concerns about inadvertent HIV status disclosure during drug collection discouraged immediate initiation, as did feeling healthy, and worries about the impact of ART initiation on relationship dynamics. Conclusion: Findings suggest that counselling messages should accurately communicate treatment risks, without perpetuating fear-based narratives about HIV. Identifying and managing patient-specific concerns and reasons for the 'need for time' may be important for supporting individuals to rapidly accept lifelong treatment. Key messages: Fear-based adherence messaging in health facilities about the dangers of missing a treatment dose or changing the time when ART is taken contributes to Zambian patients' refusals of immediate ART initiation Responsive health systems that balance a stated need for time to accept one's diagnosis and prepare to embark on a lifelong treatment plan with interventions to identify and manage patient-specific treatment related fears and concerns may support more rapid ART initiation Perceived social stigma around HIV continues to be a significant challenge for treatment initiation.